2010
DOI: 10.1074/jbc.m110.121897
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structure of the First Extracellular Domain of Corticotropin-releasing Factor Receptor 1 (ECD1-CRF-R1) Complexed with a High Affinity Agonist

Abstract: We now report the three-dimensional NMR structure of the ECD1 of human CRF-R1 complexed with a high affinity agonist, ␣-helical cyclic CRF. In the structure of the complex, the C-terminal residues (23-41) of ␣-helical cyclic CRF bind to the ECD1 of CRF-R1 in a helical conformation mainly along the hydrophobic face of the peptide in a manner similar to that of the antagonists in their corresponding ECD1 complex structures. Unique to this study is the observation that complex formation between an agonist and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 56 publications
0
34
0
3
Order By: Relevance
“…Similar 3D NMR and cocrystal structures of the CRHR 1 -ECD1 in complex with the peptide antagonist α-helical CRH 9-41 or CRH were recently disclosed (Grace et al 2010;Pioszak et al 2008). Interestingly, these studies show that complex formation between a peptide ligand and the CRHR 1 -ECD1 promotes the ligands helical conformation, thereby enhancing the ligands affinity.…”
Section: Peptide Ligands Binding Mechanismmentioning
confidence: 62%
See 1 more Smart Citation
“…Similar 3D NMR and cocrystal structures of the CRHR 1 -ECD1 in complex with the peptide antagonist α-helical CRH 9-41 or CRH were recently disclosed (Grace et al 2010;Pioszak et al 2008). Interestingly, these studies show that complex formation between a peptide ligand and the CRHR 1 -ECD1 promotes the ligands helical conformation, thereby enhancing the ligands affinity.…”
Section: Peptide Ligands Binding Mechanismmentioning
confidence: 62%
“…Recently, a considerable insight into the ligand binding mechanisms of class B GPCRs has been gained from several reports of ECD-peptide complex structures determined by NMR and X-ray methods (Grace et al 2007;Grace et al 2010;Pioszak et al 2008). The NMR solution structure of astressin (a peptide antagonist analogue based on human CRH, table 2) bound to the mouse CRHR 2 -ECD1 showed that the ECD1 consists of two antiparallel β-sheets, each with two β-strands that are held together by three conserved disulfide bonds.…”
Section: Peptide Ligands Binding Mechanismmentioning
confidence: 99%
“…The encoded fragments were digested with BamHI and NotI restriction endonucleases and inserted into a modified pcDNA6 expression vector to encode a fusion protein consisting of an N-terminal human IgG leader (MGWSCIILFL-VATATGVHSE) for targeting into the cell membrane and a FLAG tag (DYKDDDD) at the C terminus for detection by immunoblotting. In addition to the full-length receptors, we generated the same set of constructs with (i) the TMDs of GCGR (residues 123-431), GLP-1R (residues 140 -463), PTH1R (residues 182-484), CRF 1 R (residues 110 -384), and PAC1R (residues 148 -421), (ii) fusions between the N-terminal peptide hormones (glucagon (1-15), GLP-1(7-21), PTH(1-15), UNC (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), PACAP (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)) and their corresponding TMDs, (iii) fusions of the same N-terminal peptide fragments as above to the BRIL-TMD constructs, and (iv) fusions of the full-length peptide hormones to the N terminus of their corresponding full-length receptors with five copies of Gly-Ser-Ala (GSA 5 ) linker. All these constructs contain the same IgG leader as above.…”
Section: Methodsmentioning
confidence: 99%
“…Signaling-To examine the requirement of the GCGR ECD for signaling, we transiently transfected four different FLAGtagged constructs into HEK293 cells: the full-length receptor, TMD, TMD-interacting N terminus of glucagon (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) fused to the TMD, and a fusion in which glucagon (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and the TMD are separated by a thermostabilized cytochrome b562 variant, BRIL, which has been used for facilitating GPCR crystallization (16) (Fig. 1, B-D).…”
Section: Class B Gpcrs Differ In Their Ecd Requirements Formentioning
confidence: 99%
See 1 more Smart Citation